2004
DOI: 10.1024/0036-7281.146.5.233
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondrosis dissecans am Sakrum einer Berner Sennenhündin: Diagnostische und therapeutische Aspekte

Abstract: A 18-month-old female Bernese Mountain Dog with chronic pain at jumping, extension of the right hind leg and paresis of the tail was referred to the Neurological Service of the Veterinary Hospital of the University of Zurich. Upon radiological examination a mineralised fragment at the dorsal aspect of the endplate of S1 was detected. The diagnosis of Osteochondrosis dissecans was confirmed by linear and computed tomography as well as histologic examination of the fragment, which was surgically removed. Preoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Consistent with prior publications,, , osteochondrosis was observed solely in the lumbosacral joint. Young male German Shepherds were overrepresented.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with prior publications,, , osteochondrosis was observed solely in the lumbosacral joint. Young male German Shepherds were overrepresented.…”
Section: Discussionsupporting
confidence: 91%
“…Lumbosacral OCD has been described in 68 German Shepherds, 4 Boxers, 3 Rottweilers, 2 Great Danes, 2 Springer spaniels, 2 Mastiff dogs, a Newfoundland dog and a Bernese mountain dog. (Lang et al, 1992;Snaps et al, 1998;Kriegleder, 2000;Hanna, 2001;Glyde et al, 2004;Michal et al, 2004;Mathis et al, 2009). To the authors' knowledge this is the first case reported in a Beagle.…”
Section: Discussionmentioning
confidence: 92%
“…Different medical imaging modalities have been described to establish a diagnosis of lumbosacral OCD and associated cauda equina compression (Lang et al, 1992;Snaps et al, 1998;Michal et al, 2004). Although survey radiographs are very helpful in reaching a diag nosis, the superposition of the iliac wings makes it difficult to detect smaller detached fragments (Lang et al, 1992;Kriegleder, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation